Rural school enrichment program 2018 (RESAP2018) / Sayed Muhammad Aiman Sayed Abdul Khair and Nor Azizah Talkis - Sayed Abdul Khair, Sayed Muhammad Aiman; Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The main objective of this programme was to tackle issues related to lack of passion and interest towards learning among rural area students. Throughout the programme, the participants were introduced to Green Approach and En-gaging & Developmental Approach methods as strategies to enhance the participants’ level of passion and interest in learning. Various modules equipped with multiple activities were employed by the facilitators to achieve the objectives.